PPAR-γ Agonists As Antineoplastic Agents in Cancers with Dysregulated IGF Axis - Vella, Veronica; Nicolosi, Maria Luisa; Giuliano, Stefania; Bellomo, Maria; Belfiore, Antonino; Malaguarnera, Roberta (Frontiers in Endocrinology, 2017)
It is now widely accepted that insulin-resistance and compensatory hyperinsulinemia are associated to increased cancer incidence and mortality. Moreover, cancer development and progression as well as cancer resistance to traditional anticancer therapies are often linked to a deregulation/overactivation of the insulin-like growth factor (IGF) axis, which involves the autocrine/paracrine production of insulin-like growth factor (IGF-I and IGF-II) and overexpression of their cognate receptors (IGF-I receptor, IGF-IR, and insulin receptor, IR). Recently, new drugs targeting various IGF axis components have been developed. However, these drugs have several limitations including the occurrence of insulin resistance and compensatory hyperinsulinemia, which, in turn, may affect cancer cell growth and survival. Therefore, new therapeutic approaches are needed. In this regard, the pleiotropic effects of PPAR-γ agonists may have promising applications in cancer prevention and therapy. Indeed, activation of PPAR-γ by thiazolinediones or other agonists, may inhibit cell growth and proliferation by lowering circulating insulin and affecting key pathways of the Insulin/IGF axis, such as PI3K/mTOR, MAPK and GSK-3/Wnt/β-catenin cascades, which regulate cancer cell survival, cell reprogramming and differentiation. In light of these evidences TZDs and other PPAR-γ agonists may be exploited as potential preventive and therapeutic agents in tumours addicted to the activation of IGF axis or occurring in hyperinsulinemic patients. Unfortunately, clinical trials using PPAR-γ agonists as antineoplastic agents have reached conflicting results, possibly because they have not selected tumours with overactivated Insulin/IGF-I axis or occurring in hyperinsulinemic patients. In conclusion, the use of PPAR-γ agonists in combined therapies of IGFs-driven malignancies looks promising but requires future developments.